"Cut it, woman": Masculinity, Nectar, and the Orgasm in Charlotte Brontë's Shirley (1849). Issue 1 (2022) - Harrington, Christopher
Abstract : This paper identifies the theme of honey gathering in Charlotte Brontë's fiction and places it within the context of Romantic and early Victorian representations of the nectarium's role in insect-flower relationships. Brontë's novels often invert the conventional use of botany to represent female sexuality by representing men as flowers and endowing her protagonists with an ulterior form of entomological agency. These insects work to express Brontë's desire for greater economic and erotic mobility, but it is argued that this mobility is problematized by the self-absorbed nature of the masculine nectarium, a dulcet gland in flowers originally believed by botanists to ooze sugar to serve a plant's own needs. This is particularly evident in Brontë's industrial romance Shirley (1849), as the theme of honey gathering is pathologized to visualize a crisis in the plotting of Victorian femininity. This paper may be helpful to scholars interested in Brontë's fiction, representations of sexuality, botany, entomology, ecology, and early Victorian pest discourse.